Sikap Zuhud: Perspektif Hadis Tematik - Syawaluddin Nasution (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2022)
Zuhud is becoming an integral part and is not locked out. This term even also rapidly grow and practiced in the world of tasawuf which is often referred sufistik. Sufistik this not rarely is also compared to zuhud